Improving Production Technique of Mangosteen Juice Using Mangosteen Peel Extract Mixed with Tropical Fruits - Nithima Nakthong; Mohammad Naghi Eshtiaghi (Scientific Research, New Technologies and Applications Vol. 8, 2024)
Mangosteen (Garcinia mangostana L.) is one of the most common tropical fruits found in Southeast Asia and is well known for its unique taste and potential health benefits. Mangosteen fruit juice containing fruit pulp and peel with high sensory acceptance was formulated in this study. For the production of mangosteen fruit juice were different methods including enzymatic method, autoclave, and ultrasonic methods applied. The removal of the bitter taste of juice was investigated using various debittering methods. The results of this study showed that the autoclave method is the most suitable method for enhancing juice extraction from mangosteen peel. The highest juice yield (\(≈\)90% w/w) was achieved using the autoclave method followed by enzyme pre-treated (89%) and ultrasound pre-treated (\(≈\)88%) samples. In contrast, the amount of extracted Xanthone in enzyme-pre-treated pressed juice was distinct higher compared to autoclave pre-treated and enzyme-pre-treated samples. The use of calcium acetate as a successful debittering agent improved the sensory properties of the final product. The formulation of mangosteen peel juice mixed with passion fruit and orange juice offers a highly acceptable and palatable beverage, paving the way for new functional juice products. The highest juice yield (up to 90%) was achieved using the autoclave method followed by the enzyme method (89%).